2007
DOI: 10.1002/jqs.1099
|View full text |Cite
|
Sign up to set email alerts
|

The case for significant numbers of extraterrestrial impacts through the late Holocene

Abstract: When astronomers tell us that there should have been numerous impacts from space during the last five millennia, when impact craters exist on land and more impacts can be assumed over the oceans, why are historians, archaeologists and palaeoecologists not diligently seeking evidence for these impacts, and their effects? This article reviews just some of the relevant evidence for impacts. In turn this suggests that ablation material, background material from space, and micro-tektites, should all be present in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Searching for such an event is beyond the scope of this article. However, many late Holocene impacts have been documented, including one in Kiowa County, Kansas, ∼160 km northeast of the BC area, that left a 15-m-diameter crater and extensive debris field (53,61).…”
Section: Discussionmentioning
confidence: 99%
“…Searching for such an event is beyond the scope of this article. However, many late Holocene impacts have been documented, including one in Kiowa County, Kansas, ∼160 km northeast of the BC area, that left a 15-m-diameter crater and extensive debris field (53,61).…”
Section: Discussionmentioning
confidence: 99%
“…Cosmogenic tsunami: this category contains only one event that of AD 1014 when widespread flooding occurred in southeast England, Cornwall and possibly Cumbria. It has been suggested that this flooding event is a tsunami linked to a comet impact as indicated by GRIP ice core records and Chinese astronomy (Baillie, 2007). Although speculative at this stage, compelling combined historic and physical evidence persuades that an in-depth investigation should be made of this event.…”
Section: Discussionmentioning
confidence: 96%
“…Some authors consider comet sightings and impacts to be prevalent in Celtic myths and legends in Ireland and elsewhere, and link them to some historic environmental catastrophies (McCafferty and Baillie 2005). Baillie (2006Baillie ( , 2007 cites ice core data that show an anomalous peak in ammonium at AD 1014 that he considers indicates a comet impact. This is supported in that the only other ammonium peak of similar size within the last 2000 years occurs in 1908 coincident with the Tunguska bollide impact over Siberia.…”
Section: Discussionmentioning
confidence: 99%